2009
DOI: 10.1093/icb/icp080
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific profiling of gene expression informed by comparative genomic hybridization: A review and a novel approach in African cichlid fishes

Abstract: Modern genomic approaches have facilitated great progress in our understanding of the molecular and genetic underpinnings of ecological and evolutionary processes. Analysis of gene expression through heterologous hybridization in particular has enabled genome-scale studies in many ecologically and evolutionarily interesting species. However, these studies have been hampered by the difficulty of comparing-on a common array platform-gene-expression profiles across species due to sequence divergence altering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…The 45 sexbiased genes consistent between the two species are much fewer than the genes that were found to be phenotype specific (see below). Similarly, a recent study of monogamous and polygynous cichlids found that most differences in gene expression were both sex and species specific, with few genes showing sex-specific gene expression across species (Machado et al, 2009). In a previous review on the topic, Ellegren and Parsch (Ellegren and Parsch, 2007) reported that many of the genes that show sex-specific expression within species are those that are most sequence diverged between species, suggesting functional and therefore likely expression divergence.…”
Section: Sex-biased Gene Expressionmentioning
confidence: 94%
See 3 more Smart Citations
“…The 45 sexbiased genes consistent between the two species are much fewer than the genes that were found to be phenotype specific (see below). Similarly, a recent study of monogamous and polygynous cichlids found that most differences in gene expression were both sex and species specific, with few genes showing sex-specific gene expression across species (Machado et al, 2009). In a previous review on the topic, Ellegren and Parsch (Ellegren and Parsch, 2007) reported that many of the genes that show sex-specific expression within species are those that are most sequence diverged between species, suggesting functional and therefore likely expression divergence.…”
Section: Sex-biased Gene Expressionmentioning
confidence: 94%
“…In each hybridization, equal quantities of Cy3 and Cy5 samples (1.5-2.5g) were combined in hybridization buffer (Ambion SlideHyb buffer #1) and applied to the second-generation cDNA array (GEO platform ID: GLP6416) designed for the African cichlid A. burtoni (Renn et al, 2004;Salzburger et al, 2008), which contains 20,000 features, representing ~16,000 unique sequences (including 35% anonymous features) derived from brain, skin and mixed organ libraries from individuals of all ages, sexes and phenotypes, and has been validated for a variety of cichlid species (Renn et al, 2004;Aubin-Horth et al, 2007;Machado et al, 2009). Cross-species comparative genomic DNA hybridization for these Julidochromis species identified fewer than 10 microarray features that are substantially influenced by sequence or copy number differences between these species (data not shown).…”
Section: Rna Extraction and Microarray Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic basis of this behavioural variability and plasticity has recently been a focus of research using genomic and transcriptomic methods. There may be considerable sex-specific and speciesspecific gene regulation associated with breeding systems such as monogamy or polygyny [63]. In the polygynous mating system of A. burtoni, social dominance and therefore reproductive potential is associated with differences in gonad size, growth, hormone levels and coloration.…”
Section: The Genomics Of Adaptation and Speciation In Cichlidsmentioning
confidence: 99%